Efectos económicos sociales por la disolución y liquidación de las compañías de la provincia de El Oro - Alverca Merino, Vanessa del Cisne (2023)
The Curricular Integration Work titled "Economic and Social Effects of the Dissolution and Liquidation of Companies in El Oro Province" was conducted with the aim of determining the economic and social effects of companies that underwent dissolution and liquidation in El Oro Province during the period 2015-2020. An exploratory-descriptive study was conducted using a mixed-method approach, combining quantitative and qualitative methods. The design employed was non-correlational, allowing for the examination of phenomena in their natural environment without manipulation of information. Therefore, techniques such as observation, literature and documentary review, data processing and analysis, and methods such as scientific, deductive, inductive, analytical, and synthetic were implemented. The development of the study required the review of bibliographic sources and websites to obtain information on the dissolution and liquidation of companies. Various control entities were consulted to classify the information according to the study period. These entities included the Superintendence of Companies, Securities and Insurance, which provided access to the Companies Directory and the main database. Furthermore, the website of the Internal Revenue Service was utilized to determine the Income Tax declared by the companies, while the Ministry of Labor provided data on contracts made by the companies. Similarly, the Ecuadorian Institute of Social Security was used to determine the number of companies that reported employee separations, which were then classified based on their legal status and type of company. In conclusion, the Curricular Integration Work revealed that the unemployment resulting from company dissolution in Ecuador has a significant social and economic impact. It leads to increased poverty, inequality, reduced consumption, decreased tax revenue, and affects the well- being of workers and the country's development.